Blood Pressure Measurement Biases in Clinical Settings, Alabama, 2010-2011 - Keri Sewell, MD, MPH; Jewell H. Halanych, MD; Louise B. Russell, PhD (Centers for Disease Control and Prevention, 2016)
Introduction Blood pressure measurement in clinical care settings seldom follows the protocol recommended by national guidelines, potentially leading to overestimates or underestimates of blood pressure control. We evaluated blood pressure measurement methods as a source of bias in determining blood pressure control among community-dwelling adults with diabetes. Methods In a community-based trial of patients with diabetes, we measured both "clinical blood pressure" (clinical BP) (taken by a community nurse or medical assistant instructed to "take the participant's blood pressure like you do in your own clinic") and "research blood pressure" (research BP) (research staff followed a guideline-concordant protocol). Each participant had both types of blood pressure assessment on the same day over the course of 2 hours. Results The 227 participants had a mean age of 59 years; 86% were black and 74% were women. The mean clinical BP was 5 mm Hg higher than the mean research BP for systolic blood pressure (P < .001) and 2 mm Hg higher for diastolic blood pressure (P < .001). The proportion of participants whose clinical BP was 130/80 mm Hg or higher was 8 percentage points higher than the proportion whose research BP was 130/80 mm Hg or higher (P < .001), and the proportion whose clinical BP was 140/90 mm Hg or higher was 10 percentage points higher than the proportion whose research BP was 140/90 mm Hg or higher (P < .001). Among those aged 65 years or older, the proportion whose clinical BP was 130/80 mm Hg or higher was 10 percentage points higher than proportion whose research BP was 130/80 mm Hg or higher, and the proportion whose clinical BP was 140/90 mm Hg or higher was 14 percentage points higher than the proportion whose research BP was 140/90 mm Hg or higher. Whites and smokers had the greatest risk for having a clinical BP 5 mm Hg or more higher than their research BP. Conclusion Measurement biases in clinical settings may be a component of observed poor blood pressure control rates in real-world settings.